Enzymatic defense and productivity of tilapia with chemical silage and bean sprout diets - Aguilera-Morales, Martha Elena; Hernández-Sánchez, Fabiola; Domínguez-Magaña, Mario Alberto de Jesús; Antonio-Cisneros, Cynthia Magaly; Marina-Clemente, José Antonio (Ecosistemas y Recursos Agropecuarios, 2024)
After 60 days of experimentation, the effect of three diets based on chemical silage (CHS) and black bean sprouts (BS) was evaluated (DC = control diet; D1 = CHS; D2 = BS; D3 = CHS+BS) on enzymatic defense (activity of superoxide dismutase, SOD, and catalase, CAT) in the liver of tilapia, and production parameters (weight gain, protein efficiency rate, survival, feed conversion factor), prior chemical characterization of CHS, BS and the experimental diets (proximate chemical analysis, amino acids, fatty acids, anti-nutritional substances, total phenols (TPH), total flavonoids (TFl) and antioxidant capacity (AC). A randomized block design was applied with three replications using 120 masculinized GIFT tilapia juveniles of average weight of 9.6 ± 0.12 g. TPH, TFlv, and AC were analyzed by Pearson, and correlation coefficient, enzymatic activity, and productive parameters were evaluated with a one-way ANOVA and a Tukey post-hoc test (95%). Survival was 100% in all treatments and there were significant differences (p
Keywords: Oreochromis noloticus; growth; SOD; CAT; black bean sprouts